A novel non-agonist c-Met antibody drug conjugate with superior potency over a c-Met tyrosine kinase inhibitor in c-Met amplified and non-amplified cancers. Issue 6 (2nd June 2020) - Fujita, Ryo; Blot, Vincent; Wong, Eley; Stewart, Christine; Lieuw, Vincent; Richardson, Robyn; Banah, Ammar; Villicana, Jose; Timmer, Anjuli; Coronella, Julia; Newman, Roland; Gymnopoulos, Marco
ABSTRACT: c-Met is a well-characterized oncogene that is associated with poor prognosis in many solid tumor types. While responses to c-Met inhibitors have been observed in clinical trials, activity appears to be limited to those with MET gene amplifications or mutations. We developed a c-Met targeted antibody-drug conjugate (ADC) with preclinical activity in the absence of MET gene amplification or mutation, and activity even in the context of moderate protein expression. The ADC utilized a high-affinity c-Met antibody (P3D12), that induced c-Met degradation with minimal activation of c-Met signaling, or mitogenic effect. P3D12 was conjugated to the tubulin inhibitor toxin MMAF via a cleavable linker (vc-MMAF). P3D12-vc-MMAF demonstrated potent in vitro activity in c-Met protein-expressing cell lines regardless of MET gene amplification or mutation status, and retained activity in cell lines with medium-low c-Met protein expression. In contrast, the c-Met tyrosine kinase inhibitor (TKI) PHA-665752 slowed tumor cell growth in vitro only in the context of MET gene amplification or very high protein expression. This differential activity was even more marked in vivo. P3D12-vc-MMAF demonstrated robust inhibition of tumor growth in the MET gene amplified MKN-45 xenograft model, and similar results in H1975, which expresses moderate levels of wild type c-Met without genomic amplification. By comparison, the c-Met TKI, PHA-665752, demonstrated modest tumor growth inhibition in MKN-45, and no inhibition at all in H1975. Taken together, these data suggest that P3D12-vc-MMAF may have a superior clinical profile in treating c-Met positive malignancies in contrast to c-Met pathway inhibitors.